Experimental Study on In-Plane Seismic Performance of Reinforced Brick Walls Bonded with Mud - Hui Wang; Jian-jun Chang; Shi-qin He; Qing-lei Zhang (Advances in Civil Engineering)
Low-cyclic loading tests were carried on brick walls bonded with mud reinforced by three methods: packing belts, one-side steel-meshed cement mortar, and double-side steel-meshed cement mortar. The failure modes, hysteresis curves of the load-displacement, skeleton curves, and ductility were obtained. The results showed that the bearing capacity of the brick walls bonded with mud reinforced by the abovementioned three methods had been increased to 1.4, 1.7, and 2.2 times as much as that of the unreinforced brick walls, respectively, and the ductility of the reinforced brick walls had been increased to 4.7, 2.1 and 2.2 times, respectively. The integrity and ductility of the reinforced brick walls were effectively improved in different degrees. The experimental results provided specific seismic strengthening techniques for the farmhouses built with brick walls bonded with mud.